2020
DOI: 10.31083/j.jin.2020.02.1246
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant pathways of the Chinese herb jiaweisinisan through genetic ontology analysis

Abstract: Active compounds and corresponding targets of the traditional Chinese herb, jiaweisinisan, were obtained from systems pharmacological database and placed into ClueGO for gene ontology analysis. The targets of depression were obtained from the Online Mendelian Inheritance in Man, the Therapeutic Target Database, and the Pharmacogenomics Knowledge Base. Compound-target and target-pathway networks were constructed using Cytoscape, and then their topological parameters were analyzed. The targets of jiaweisinisan a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…For example, Bangpungtongsung-San was shown to reduce levels of nitric oxide (NO), inducible nitric oxide synthase (iNOS), cyclooxygenase (COX)-2, tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), and interleukin-6 (IL-6) in a dose-dependent manner via decreased expression of nuclear factor (NF)-κB p65, which suggested that its antidepressant effects were likely related to the suppression of neuroinflammation ( Park et al, 2020 ). By contrast, the antidepressant mechanisms of Jiaweisinisan appeared to be associated with regulating immune-mediated inflammation, cell apoptosis and synaptic transmission ( Chen et al, 2020 ). In addition, Xiaoyaosan exhibited synergistic antidepression effects by adjusting Caspase-3 and Nitric oxide synthase-3 ( Liu et al, 2021 ).…”
Section: Herbal Therapies For Depressive Disordersmentioning
confidence: 99%
“…For example, Bangpungtongsung-San was shown to reduce levels of nitric oxide (NO), inducible nitric oxide synthase (iNOS), cyclooxygenase (COX)-2, tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), and interleukin-6 (IL-6) in a dose-dependent manner via decreased expression of nuclear factor (NF)-κB p65, which suggested that its antidepressant effects were likely related to the suppression of neuroinflammation ( Park et al, 2020 ). By contrast, the antidepressant mechanisms of Jiaweisinisan appeared to be associated with regulating immune-mediated inflammation, cell apoptosis and synaptic transmission ( Chen et al, 2020 ). In addition, Xiaoyaosan exhibited synergistic antidepression effects by adjusting Caspase-3 and Nitric oxide synthase-3 ( Liu et al, 2021 ).…”
Section: Herbal Therapies For Depressive Disordersmentioning
confidence: 99%